Charged dust in the D-region incoherent scatter spectrum - Gunnarsdóttir, Tinna Líf; Mann, Ingrid (Journal of Plasma Physics, 2021)
We investigate the influence of charged dust on the incoherent scatter from the D-region ionosphere. Incoherent scatter is observed with high-power, large aperture radars and results from electromagnetic waves scattering at electrons that are coupled to other charged components through plasma oscillations. The influence of charged dust can hence be considered an effect of dusty plasma. The D-region contains meteoric smoke particles that are of nanometre size and form from incoming ablating meteors. Detection of such charged dust in the incoherent scatter spectrum from the D-region has previously been proposed and studied to some degree. We here present model calculations to investigate the influence of the charged dust component with a size distribution, instead of the one size dust components assumed in other works. The developed code to calculate the incoherent scatter spectrum from the D-region including dust particles with different sizes and different positive and negative charge states is made available (https://doi.org/10.18710/GHZIIY). We investigate how sizes, number density and charge state of the dust influence the spectrum during different ionospheric conditions. We consider the ionospheric parameters for the location of the EISCAT VHF radar during a year and find that conditions are most suitable for dust detection in winter below 80 km at times with increased electron densities. The prospects to derive dust parameters increase, when the incoherent scatter observations are combined with those of other instruments to provide independent information on electron density, neutral density and temperature.